Automatic Fish Feeding and Temperature Control System for Aquariums Based on Internet of Things (IoT) - Widyati, Made Ayu Sri; Anshori, Yusuf; Lamasitudju, Chairunnisa Ar.; Laila, Rahmah; Joefrie, Yuri Yudhaswana (Journal of Applied Informatics and Computing, 2025)
Keeping fish in aquariums has become one of the people's hobbies. An important factor in fish maintenance is the process of feeding and controlling the temperature of the aquarium. However, with various activities, fish care is often not carried out properly. This study develops an automatic system for feeding and controlling the temperature of the aquarium with goldfish as the test object. This study designs an automatic system to control the temperature and feeding in the aquarium using hardware such as a DS18B20 temperature sensor, load cell, and ultrasonic sensor. This system is controlled by ESP32 for reading sensor data and Arduino Uno for controlling the relay, cooling system, heater, and servo motor. ESP32 reads sensor data and sends it via MQTT to Node-red. Based on this data, the system regulates the temperature by activating the cooler (peltier and water pump) if the temperature is >28℃ and turning off the cooler when the temperature is <26℃. The heater is active if the temperature is <24℃ and stops when the temperature reaches 26℃. Feeding is carried out according to schedule, with servo 1 dropping feed into the load cell until the weight reaches the target weight. After that, servo 2 moves the feed into the aquarium. If the weight has not reached the target, servo 1 continues to be active. Based on the test, the average percentage of error in the temperature sensor is 0,08%, the weight sensor is 1.10%, and the ultrasonic sensor is 1.61%. This system successfully performs four times a day feeding and controls the temperature within the optimal range for goldfish, which is 24-28℃. The test results show that this system functions well and is in accordance with the research objectives.